Incidence and predictors of HBV functional cure in patients with HIV/HBV coinfection: A retrospective cohort study - Zhang, Qingrong; Wang, Hu; Jin, Yi; Zhou, Na; Sun, Lijun; Wu, Hao; Chen, Haitao; Jiang, Taiyi (Frontiers in Cellular and Infection Microbiology, 2023)
Background This study was the first to examine the association of baseline clinical factors with the rate of HBsAg clearance in a large retrospective cohort of Chinese patients with HIV/HBV coinfection treated with combination antiretroviral therapy (ART). Methods Our retrospective cohort included 431 patients with HIV/HBV coinfection treated with TDF-containing ART. The median follow-up was 6.26 years. Logistic regression was used to investigate the association of baseline variables with HBsAg clearance, and Cox regression was used to investigate the association of baseline variables with time to HBsAg clearance. Results The clearance rate of HBsAg in our study was 0.072 (95% CI 0.049 0.101). In the multivariate logistic regression, advanced age (OR=1.1, P=0.007), high CD4 cell count (OR=2.06, P=0.05), and HBeAg positivity (OR=8.00, P=0.009) were significantly associated with the rate of HBsAg clearance. The AUC of the model integrating the above three predictors was 0.811. Similar results were found in the multivariate Cox regression (HR = 1.09, P = 0.038 for age, HR = 1.05, P = 0.012 for CD4 count and HR = 7.00, P = 0.007 for HBeAg). Conclusions Long-term TDF-containing ART can lead to HBsAg clearance of 7.2% in Chinese patients with HIV/HBV coinfection. Advanced age, high CD4 cell count, and positive HBeAg at baseline could be regarded as potential predictors and biological markers for HBsAg clearance in patients with HIV/HBV coinfection.